Pengaruh Kompaksi dan Kandungan Grafit Terhadap Karakteristik Mekanis Bantalan Luncur Connecting Rod - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Bearing is an important component in the automotive industry that is needed to be made of material having good properties. Aluminum graphite matrix composite becomes a selected tribology application in self-lubricating bearing. This composite hasgood wear resistance and low density compared with bronze bearing material so that gives more economical values. This research is done by the method of powder metallurgy with aluminu,!, matrix composite material using an additive of 5% graphite weight fraction. Variable compactions (P) are 400 MPa, 500 MPa, 600 MPa and sintering temperature is 55dJc, ~ith variable holding times (HT) 1 hour, 2 hours and 3 hours. The study aims to analyze the effect of graphite content affecting the mechanical properties of aluminum graphite composite material. The test results show that the optimum condition of 5% graphite content is the density = 5.11 gr/cm3, the hardness = 54.449 HB, the compressive strength = 790 MPa, when P = 600 MPa and lIT = 3 hours. Keywords: aluminium, komposit, serbuk, kompaksi, holding time.